PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI, DAN PENGEMBANGAN KARIERTERHADAP KINERJA KARYAWAN (STUDI PADA CV. JORDAN SEMARANG) - Lisna Ayu Ardiyani, 11.05.51.0035 (Students Journal of Economic and Management, 2015)
This study analyzed the effect of transformational leadership, motivation, and development of Karier on theÂ  employee performance. Object of study in this paper isÂ  CV. Jordan Semarang. The sampling technique in this research use the Simple Random Sampling by 50 respondents. Analysis of the data used include the product moment test validity, reliability testing with Alpha Cronbrach, multiple regression analysis, t test to test and aprove the research hypothesis. The results of the research are: (1) Transformational Leadership give positive and significant impact on the performance of the employee, the better leadership within the organization will improve employee performance.(2) Motivation have positive and significant impact on the performance of the employee, the more often the motivation is given it will improve employee performance.(3) Career Development hasnât impactÂ  for the performance of the employee, getting better career position is given so the employee will be increased. Keywords: work Transformational Leadership, Motivation, carrier development and employee Performance.